Social Interaction and self-Confidence Development of Students in Discussions-Based and Role-Play Speaking Learning - Sri Erna Nurmalia (Indonesian Journal Education, 2025)
Speaking is an important skill in learning English, especially for students from non-English departments such as the Islamic Religious Education Study Program at the Az Zahra Tasikmalaya Islamic Boarding School. Students from Islamic boarding schools and rural areas generally face challenges in speaking English because they are not accustomed to using the language in their daily lives. This study aims to describe the role of social interaction in building student self-confidence through discussion-based and role-play speaking activities. This study uses a qualitative phenomenological approach, with research subjects consisting of third-semester students of the Islamic Religious Education Study Program at the Az Zahra Tasikmalaya Islamic Boarding School. Data were collected through participant observation, in-depth interviews, and documentation of learning activities, then analyzed using an interactive model that includes data condensation, data presentation, and conclusion drawing. The results show that discussion-based and role-play speaking learning can create an interactive, enjoyable learning atmosphere and support the growth of student self-confidence. Through social interaction in small groups, students become more confident in speaking, support one another, and feel safe when making mistakes. Role-play activities help students practice speaking naturally without pressure, while the lecturer’s empathetic and supportive attitude strengthens motivation and reduces speaking anxiety.